Radiomitigative Effects of Approved Hematopoietic Drugs on Mice Exposed to Lethal Total-body Irradiation - T. Nishida; M. Yamaguchi; S. Miura; K. Waga; N. Kawabata; M. Syaifudin; I. Kashiwakura (PPIKSN-BATAN, 2020)
In cases of radiological accidents, especially for victims exposed to high-dose total-body irradiation (TBI), the administration of appropriate approved hematopoietic drugs is the most rapid medical treatment for preventing severe acute radiation syndrome, which is associated with a high mortality rate. However, at present, there are few suitable pharmaceutical drugs available in Japan, aside from granulocyte colony-stimulating factor (G-CSF). Depending on the situation surrounding the accident, various drug treatment options and the development of effective drug therapies may be required. In the present study, we assessed various combinations of seven commercially available drugs-G-CSF, erythropoietin (EPO), romiplostim (RP), ancer (AN), cepharanthine (CE), leucon (LC) and leukoprol (LP)-in mice exposed to a lethal dose of 7 or 8 Gy of X-ray irradiation. Each drug was administered as a single or mixed intraperitoneal injection once or twice daily for three consecutive days. The single administration of the approved hematopoietic drugs CE, LC, or LP twice a day for 3 days significantly improved the 30-day survival rate of lethal TBI mice (p < 0.05; 75%, 100%, or 100%, respectively) compared with the untreated TBI mice, accompanied by a gradual increase in the body weight. Furthermore, the combined administration of RP, EPO and G-CSF or single administration of RP alone gradually increased the body weight of mice exposed to lethal TBI, with 30-day survival rates of 75% or 100%, respectively (p < 0.05). This study suggested that some new domestically approved hematopoietic drugs may have radiomitigative potential for mice exposed to lethal TBI, and the 12-h interval administration of LC or LP for 3 days to 7-Gy-TBI mice and 12-h interval administration of RP alone for 3 days to 8-Gy-TBI mice were the most suitable medications with respect to the 30-day survival rate. As long as the threat of nuclear disaster exists, diverse efforts in thefield of radiation emergency medicine, including the development of effective drug therapies, will be necessary.